2022
DOI: 10.3389/fmed.2022.985803
|View full text |Cite
|
Sign up to set email alerts
|

Depression in non-alcoholic fatty liver disease is associated with an increased risk of complications and mortality

Abstract: Background and aimsThe global prevalence of non-alcoholic fatty liver disease (NAFLD) is expected to rise continuously. Furthermore, emerging evidence has also shown the potential for concomitant depression in NAFLD. This study aims to examine the prevalence, risk factors, and adverse events of depression in NAFLD and evaluate whether treated depression can reverse the increased risks of adverse outcomes.Materials and methodsThis study analyses the 2000–2018 cycles of NHANES that examined liver steatosis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…It is important to highlight that there could be many other factors that may contribute to the mental health and well-being of patients with NAFLD, including symptoms of fatigue which may impact on quality of life and the high risk of significant complications, as well as the lack of awareness of the condition and perceived stigmatization ( 28 ). Furthermore, it is reported that NAFLD patients with depression are at a greater risk of adverse outcomes, such as stroke, CVD and cancer-related mortality compared to those without depression ( 90 ). Similarly, anxiety has been shown to be associated with a number of health issues including CVD, hypertension and gastrointestinal issues ( 91 ), and increased levels of anxiety among NAFLD patients might also lead to further physical complications.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to highlight that there could be many other factors that may contribute to the mental health and well-being of patients with NAFLD, including symptoms of fatigue which may impact on quality of life and the high risk of significant complications, as well as the lack of awareness of the condition and perceived stigmatization ( 28 ). Furthermore, it is reported that NAFLD patients with depression are at a greater risk of adverse outcomes, such as stroke, CVD and cancer-related mortality compared to those without depression ( 90 ). Similarly, anxiety has been shown to be associated with a number of health issues including CVD, hypertension and gastrointestinal issues ( 91 ), and increased levels of anxiety among NAFLD patients might also lead to further physical complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ng et al reported a risk of depression for individuals with NAFLD was 12% higher than that for those without NAFLD [ 29 ]. In another study, patients with NAFLD had a significantly higher risk of depression (OR = 1.13) than did those without NAFLD, and patients with depression had a significantly higher risk of developing NAFLD (OR = 1.46) than did those without.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that NAFLD and depression are highly correlated and can interact [ 30 ]. Because concurrent depression in NAFLD can amplify the likelihood of negative health consequences, Ng et al suggested that early screening for depression in high-risk individuals with NAFLD can improve their well-being [ 29 ]. Two population-based studies have demonstrated strong associations between depression and HZ, indicating that the HR of depression for HZ development is 1.1 (compared with no depression) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adiposity and dysregulation of adipose tissue lipid metabolism in NAFLD are thought to be involved in the pathogenesis of depression, suggesting an important role for obesity and adipose tissue function in the liver-brain axis in NAFLD [18, 19. ] Depression and NAFLD co-morbidity were signi cantly associated with an increased prevalence of CVD and risk of mortality compared to individuals with NAFLD not experiencing depression [20]. Therefore, identifying modi able risk factors for depression in NAFLD patients is clinically crucial.…”
Section: Introductionmentioning
confidence: 99%